Psychometric Properties of the SAS, BAI, and S-AI in Chinese University Students - Pang, Zhanyu; Tu, Dongbo; Cai, Yan (Frontiers in Psychology, 2019)
Three widely-used self-report anxiety scales, including the Self-Rating Anxiety Scale (SAS), the Beck Anxiety Inventory (BAI) and the State Anxiety Inventory (S-AI), were used to simultaneously compare the psychometric properties via an IRT model in a Chinese university student sample. Although the scales were likely to measure the same underlying construct-anxiety, the psychometric properties of them were very different. Results showed that, the BAI’s measurement error was smaller than that of the other scales at the range of anxiety severity approximately from the 0.8 standard deviations below the mean to 3 standard deviations above the mean, while the S-AI’s measurement error was smaller than that of the other degrees of anxiety. The S-AI provided more information than the other scales when the student’s scale was less than approximately 0.8 standard deviations below the mean of anxiety severity. The BAI performed better as a whole, as it provided more information than the other scales at the broadest range of anxiety severity. The SAS provided less information than the other scales at all anxiety severity range. In conclusion, BAI shows good psychometric quality. Finally we linked the three instruments on a common scale by using IRT model and provided a conversion table to enable the transformation of each scale score.